Clinical nurse specialist role implementation structures, processes and outcomes: Participatory action research. Issue 15 (5th May 2021) - Jokiniemi, Krista; Korhonen, Kristiina; Kärkkäinen, Anne; Pekkarinen, Tuomo; Pietilä, Anna‐Maija
Abstract: Aim: To develop, implement and evaluate the clinical nurse specialist's role within a specialist medical healthcare hospital. A secondary aim was to assess the feasibility of the 'Clinical Nurse Specialist Conceptualisation, Implementation, and Evaluation framework' in the role implementation. Background: Implementation of advanced practice nursing roles is an increasing practice around the globe; however, the implementation of these roles is multidimensional, complex process. Clear implementation strategies are needed. Design: Participatory action research was conducted in Finland between 2017–2018. Methods: The researchers adopted an outsider approach to work with staff, considered as co‐researchers, within two participating units. A combination of several methods, such as focus group interviews, action‐learning groups and researcher reflective field journal, was used to gather data. The 'Clinical Nurse Specialist Conceptualisation, Implementation, and Evaluation framework' was used to structure the processes undertaken, and the Donabedian structure, process and outcome model was used to structure and analyse the results. The study was reported using the EQUATOR guideline for participatory action research. Results: The results demonstrated the complexity of the role implementation process. Four implementation themes of need analysis, role design, role implementation and role evaluation were examined and described through their structures, processes and outcomes. The 'Clinical Nurse Specialist Conceptualisation, Implementation and Evaluation framework' was validated for its appropriateness guiding the role implementation process. Conclusions: Role implementation is a complex process which structured, practical guidelines may facilitate. The examined framework may facilitate the role implementation process conducted within organisations. Relevance to clinical practice: This research provides complimentary information for individuals and organisations aiming to develop a clinical nurse specialist or other advanced practice nursing roles. Furthermore, we describe a participatory action research process, which offers the means for self‐reflection and planning of purposeful actions to improve the conditions of clinical practice.